2018
DOI: 10.1111/jocn.14348
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and implementation of evidence‐based practice among community health nurses: A cross‐sectional descriptive study

Abstract: These results revealed the level of implementation of evidence-based practice by nurses in community healthcare settings in Valais. Further research is required to better understand their needs and expectations and to develop suitable strategies that will allow the integration of evidence-based practice into nurses' daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
17
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 40 publications
12
17
0
4
Order By: Relevance
“…In this study, it was observed that nurses who attended scientific events had more positive attitudes towards evidence-based nursing than nurses who do not. Similar results were obtained in some studies (Ayhan et al 2015;Stavor et al, 2017;Pereira et al, 2018). This made us think that nurses who conduct scientific research learned the importance of evidence-based practices on their own while doing research, and that the learning about evidence-based practices from other colleagues in scientific events they attended may also be effective in their positive attitudes.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, it was observed that nurses who attended scientific events had more positive attitudes towards evidence-based nursing than nurses who do not. Similar results were obtained in some studies (Ayhan et al 2015;Stavor et al, 2017;Pereira et al, 2018). This made us think that nurses who conduct scientific research learned the importance of evidence-based practices on their own while doing research, and that the learning about evidence-based practices from other colleagues in scientific events they attended may also be effective in their positive attitudes.…”
Section: Discussionsupporting
confidence: 86%
“…[10] One study [39] found that 97% respondents agreed or strongly agreed on the promotive role of EBP in patient care, while only 5% by learning the skills of EBP and 2% by seeking and applying evidence-based summaries established evidence-based implementation. Pereira et al [45] discovered CNs got higher scores of believing in EBP will improve care (4.02), but the implementation of EBP sufficiently got relatively lower scores (2.71). Similar findings [35] of poor implementation were also reported in Canada, as 7% respondents formulated questions and performed knowledge search, 20% used database, and 22% used research in practice.…”
Section: Resultsmentioning
confidence: 99%
“…AFs were also recorded in Swiss community healthcare settings by Pereira et al (2018) and hospital settings by Verloo et al (2017b).…”
Section: Discussionmentioning
confidence: 99%